2016
DOI: 10.1016/j.cej.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide adsorption by zinc-functionalized ionic liquid impregnated into bio-templated mesoporous silica beads

Abstract: Carbon dioxide adsorption by zincfunctionalized ionic liquid impregnated into bio-templated mesoporous silica beads, Chemical Engineering Journal (2015), doi: http://dx. AbstractNovel high capacity hybrid sorbents for CO 2 capture have been developed based on zincfunctionalized ionic liquid (IL) impregnated into mesoporous silica beads derived from calcium alginate template beads. Pore modification and development of a surface-confined layer of IL synergistically enhanced the uptake capacity (up to 8.7 wt%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 73 publications
4
34
0
Order By: Relevance
“…The [BMIM]PF 6 @aerosil has BET surface area of 59.66 m 2 /g with pore radius ∼ 1446.3 A ° which was comparatively less in comparison with the pristine aerosil (200 m 2 /g) . The decrease in the BET surface area provides indirect evidence for confinement of ionic liquid on the surface of aerosil …”
Section: Resultsmentioning
confidence: 99%
“…The [BMIM]PF 6 @aerosil has BET surface area of 59.66 m 2 /g with pore radius ∼ 1446.3 A ° which was comparatively less in comparison with the pristine aerosil (200 m 2 /g) . The decrease in the BET surface area provides indirect evidence for confinement of ionic liquid on the surface of aerosil …”
Section: Resultsmentioning
confidence: 99%
“…Inherently, PC also contains labile −Cl atoms in the form of defect allylic chlorine sites, −CH 2 −(RCCl)−CH=CH 2 −, which are incorporated into the polymer structure during PC synthesis. It was reported that appreciable reaction of these sites with diamine molecules occurred at 70 °C after 10–14 h . However, these allylic sites should comprise only ca.…”
Section: Figurementioning
confidence: 99%
“…However, due to the major disadvantages like high cost, low efficiency and inapplicability to remove a vast range of pollutants, most of them did not receive wide acceptance (Gupta, Agarwal, Singh, & Pathania, 2013). Conversely, adsorption, particularly based on sorbents of both mineral, organic and biological origins such as activated carbons (Hadi et al, 2015;Shen, Ma, Mei, & Zhang, 2010), zeolites (Andrejkovičová et al, 2016;Mudasir, Karelius, Aprilita, & Wahyuni, 2016), clays (Cantuaria, de Almeida Neto, Nascimento, & Vieira, 2016;Ji et al, 2015), silica beads (Arellano, Madani, Huang, & Pendleton, 2016;Ghoul, Bacquet, & Morcellet, 2003), industrial by-products (Bhatnagar, Jain, Minocha, & Singh, 2006;Joshi et al, 2015), agricultural wastes (Hegazi, 2013;Nguyen et al, 2013), biomass (Lingamdinne, Yang, Chang, & Koduru, 2015;Singha & Guleria, 2014) and polymeric materials including organic polymeric resins L. Zhou, Shang, Liu, Huang, & Adesina, 2012), macroporous hypercrosslinked polymers (Azanova & Hradil, 1999;X.…”
Section: Introductionmentioning
confidence: 97%